(untitled) (Global Journal of Medical Research, 2020)
The scientific work presents the results of neurophysiological examination of 207 patients with Chiari malformation of type 1 according to MRI data. All patients underwent a multimodal protocol, including acoustic stem evoked potentials, somatosensory evoked potentials, and electroneuromyography. The diagnostic criteria for neurological syndromescerebellar, bulbar, pyramidal, syringomyelitis in Chiari malformation of type 1 according to neurophysiological data -were identified. A clinical and neurophysiological point scale for the choice of conservative or surgical tactics has been proposed.